Adapting Challenge-Based Learning Model in Islamic Religious Education to Improve Students' Religious Attitudes in Secondary School - Nasrudin, Ega; Kosasih, Aceng; Rahmat, Munawar; Supriadi, Udin; Firmansyah, Mokh. Iman; Anwar, Saepul (Tadbir : Jurnal Studi Manajemen Pendidikan, 2025)
Learning models have an important role in achieving success in achieving goals. This study aims to examine the Challenge Based Learning model and compile its implementation in Islamic Religious Education Learning to Increase Student Religiosity as the core objective of Islamic Religious Education learning. The approach in this research uses a qualitative approach with the type of literature study. The data in this study were obtained from primary sources including Challenge Based Learning Guidelines, Textbooks, and Education Regulations in Indonesia. In addition, this study also took secondary sources from various relevant scientific journal articles. The data obtained was then analyzed with the stages of data reduction, data presentation, and conclusion drawing. The result of this study concludes that the Challenge Based Learning (CBL) model is an innovative approach that places learners as the main subject in designing real solutions to challenges relevant to their lives. CBL not only encourages active engagement, collaboration, and the development of 21st century competencies such as critical thinking, creativity, communication, and collaboration, but it is also very relevant to be implemented in Islamic Religious Education Learning to improve students' substantive religiosity. Through a systematic syntax, starting from the engage, explore, to act stages, CBL helps learners identify, analyze, and solve real problems reflectively and applicatively. Thus, the application of CBL in Islamic Religious Education learning has the potential to form a religious character that is not only symbolic, but also reflected in students' daily behavior, so as to overcome various phenomena of moral decline and religiosity in the current educational environment. Researchers in this case recommend further research in the form of implementing the Challenge Based Learning model in Islamic Religious Education Learning to Improve Students' Religious Attitudes.